The Role of the Village Government's Commitment in Moderating the Relationship Between Community Participation, Financial Transparency, and the Use of Information Technology on the Financial Management of Village Funds in Dresi Kulon Village, Rembang Regency - Haningtyas, Selly Lofiana; Puspitasari, Diana; Prayitno, Agus; Oktoriza, Linda Ayu (Dinasti Publisher, 2026)
This study examines the influence of community participation, financial transparency, and information technology utilization on Village Fund financial management, with village government commitment as a moderating variable in Dresi Kulon Village, Rembang. The methodology used was a quantitative approach, analyzing questionnaire data collected from 146 participants and then processing it using SEM–SmartPLS. The results show that community participation, financial transparency, and information technology utilization have a positive impact on Village Fund financial governance, with financial transparency having the strongest impact, while village government dedication was shown to mediate the relationship between financial transparency and IT utilization. This framework was able to explain 47.0% of the change in Village Fund financial management (R² = 0.470). Therefore, it is recommended to strengthen financial reporting transparency, village government commitment, and technology utilization.